Image encryption using dna-sequences, chaotic dynamics and hash fuctions - A. V. Sidorenko; M. S. Shishko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An image encryption algorithm based on DNA-sequences, chaotic dynamics and hash functions is described. It is evaluated the resistance of the investigated algorithm to statistical and linear cryptanalysis which are depended of the chaotic maps.